Structural and Mechanistic Features of Phospholipases C: Effectors of Inositol Phospholipid-Mediated Signal Transduction - James, Stephen R.; Downes, C.Peter (Cellular Signalling, 1997)
The production of the intracellular second messengers inositol (1,4,5)-trisphosphate (InsP 3) and sn 1,2-diacylglycerol (DG) in response to a wide variety of extracellular primary messengers is achieved by an extended family of inositol phospholipid phosphodiesterases termed phospholipases C (PLC, E.C. 3.1.4.11). This family has been the subject of extensive research and it is clear that the different isoenzymes exhibit some common characteristics (e.g., interactions with substrates) and other distinctive features (e.g., modes of regulation). The recent description of the X-ray crystal structure of a mammalian PLC has served to clarify much about the behaviour of the PLCs, emphasising the “modular” structure of these enzymes. The main focus of this review will concern the specific adaptations of PLC molecules which make them efficient lipid-metabolising enzymes. We also describe what is known about how these enzymes interact with their lipid substrates, which will serve as a basis for considering how PLCs may be activated.